Aetiology, course and treatment of acute tubulointerstitial nephritis in paediatric patients: a cross-sectional web-based survey. Issue 5 (28th May 2021) - Wente-Schulz, Sarah; Aksenova, Marina; Awan, Atif; Ambarsari, Cahyani Gita; Becherucci, Francesca; Emma, Francesco; Fila, Marc; Francisco, Telma; Gokce, Ibrahim; Gülhan, Bora; Hansen, Matthias; Jahnukainen, Timo; et al.
Abstract : Background: Acute tubulointerstitial nephritis (TIN) is a significant cause of acute renal failure in paediatric and adult patients. There are no large paediatric series focusing on the aetiology, treatment and courses of acute TIN. Patients, design and setting: We collected retrospective clinical data from paediatric patients with acute biopsy-proven TIN by means of an online survey. Members of four professional societies were invited to participate. Results: Thirty-nine physicians from 18 countries responded. 171 patients with acute TIN were included (54% female, median age 12 years). The most frequent causes were tubulointerstitial nephritis and uveitis syndrome in 31% and drug-induced TIN in 30% (the majority of these caused by non-steroidal anti-inflammatory drugs). In 28% of patients, no initiating noxae were identified (idiopathic TIN). Median estimated glomerular filtration rate (eGFR) rose significantly from 31 at time of renal biopsy to 86 mL/min/1.73 m 2 3–6 months later (p<0.001). After 3–6 months, eGFR normalised in 41% of patients (eGFR ≥90 mL/min/1.73 m 2 ), with only 3% having severe or end-stage impairment of renal function (<30 mL/min/1.73 m 2 ). 80% of patients received corticosteroid therapy. Median eGFR after 3–6 months did not differ between steroid-treated and steroid-untreated patients. Other immunosuppressants were used in 18% (n=31) of patients, 21 of whom received mycophenolate mofetil. Conclusions: Despite different aetiologies, acute paediatric TIN had a favourable outcome overall with 88% of patients showing no or mild impairment of eGFR after 3–6 months. Prospective randomised controlled trials are needed to evaluate the efficacy of glucocorticoid treatment in paediatric patients with acute TIN.